Acoustic Energy Harvester by Electromagnetic Mechanisms and Helmholtz Resonator. Issue 1 (December 2020) - Gu, Cong; Chen, Yuansheng; Chen, Wei; Zhao, Pengcheng
Abstract: In order to harvest the acoustic energy in the environment, an electromagnetic acoutic energy harvest system is proposed based on Helmholtz resonator, coil, permanent magnet and interface circuit. When the sound wave is injected into the resonator, it causes the upper surface permanent magnet to vibrate and outputs electrical energy from the coil. The resonant frequency of the resonator is simulated and analysed by finite element method, the interface circuit is simulated and analysed, the acousto-electric conversion principle is analysed theoretically. The output characteristics of the system under different frequencies and sound pressure levels are studied by experiments, and the output characteristics of the system after using the interface circuit are studied. The experimental results show that the system can harvest the acoustic energy of different frequencies, and the power generation effect is better when the acoustic frequency is near 98Hz and 140Hz, which is close to the first two resonant frequencies of the system. The output voltage and power of the system increase with the increase of the sound pressure level. When the sound pressure level is lower than 105dB, the output voltage and power of the system under the acoustic frequency of 95Hz is higher, and when the sound pressure level is greater than 105dB, the output voltage and power of 140Hz acoustic frequency is higher. After using the interface circuit, the maximum open-circuit voltage is 13.65V when the sound pressure level is 110dB and the frequency is 98Hz, and the maximum output power of the system can reach 0.625mW when the sound pressure level is 110dB and the frequency is 140Hz.